Career transition antecedents in the information technology area. (11th September 2015) - Joia, Luiz Antonio; Mangia, Ursula
Abstract: The more organizations invest in information technology (IT), the more the concern with IT personnel management has increased, namely the hiring, training and retaining of IT professionals needed to deal with such investments. In this context, two issues related to these professionals have often been observed, namely 'turnover' – in which the IT professional changes job but still remains in the IT area – and 'turnaway' – in which the IT professional abandons the IT area and assumes a job in another area in the same organization or another, usually rising to a managerial position. This work addresses the turnaway of IT professionals in Brazil. The relevance of this research is supported by the shortage of adequately trained IT professionals to work in the productive sector in this country. Therefore, by using and adapting the extant scientific literature, research hypotheses associated with the IT professional turnaway phenomenon are developed and tested via structural equation modelling. It was then concluded that exhaustion with work in the IT area, job dissatisfaction, the need to acquire further experience to remain attractive in the job market, the need for professional growth and prior and conscious managerial capacity development for career transition are the main antecedents of the career transition of IT professionals to other functional areas.